The impacts of perceived government market orientation and social media travel influencers' attributes on domestic tourists' visit intention to Chongqing City : The mediating role of trust - Wu, Tang (2025)
In China, cities such as Chongqing and Xi'an are rapidly gaining popularity through social media platforms, attracting widespread attention, discussion, and a large influx of tourists. This surge in city tourism is driven not only by government marketoriented strategies but also by the social media travel influencers (SMTIs). However, limited research explores the extent to which tourists’ visit intentions are influenced by perceived government market orientation (PGMO) and SMTIs. The objectives of this study, therefore, aim to examine the relationships between perceived government market orientation (PGMO), SMTIs’ attributes, and tourists’ visit intentions to Chongqing. In addition, the study also investigates the mediating role of trust between the SMTIs’ attributes and visit intention. The research focuses on Chinese domestic tourists who have never visited Chongqing but are SMTIs followers in social media. To explain these relationships, the study employs the Stimulus- Organism-Response (SOR) model and source credibility theory as the theoretical frameworks. Data are collected through a self-administered questionnaire, using purposive sampling targeting followers on two major social media platforms, Douyin and Sina Weibo. Structural equation modelling (SEM) is conducted on 409 valid responses using SPSS (version 27) and AMOS (version 26). The results indicated that all independent variables, including PGMO, SMTIs’ expertise, authenticity, and physical attractiveness, have positive relationship with tourists’ visit intentions. In terms of indirect relationships, the findings revealed that trust positively mediates the relationship between SMTIs’ authenticity, SMTIs’ expertise, and tourists' visit intentions. However, SMTIs’ physical attractiveness does not influence visit intentions through trust. This study enriches current research understanding by introducing a structural model that combines PGMO and SMTIs, with trust as a mediator to analyse tourists' visit intentions. Additionally, this research provides valuable insights for city governments and destination marketing organizations, helping them understand tourists’ perceptions of government market orientation, SMTIs, and trust. The study suggests prioritizing these elements to promote city tourism growth in the age of social media